Simultaneous electrochemical leaching, enrichment, and recovery of phosphorus as value-added vivianite from poly-aluminum chloride (PAC) sludge - Hongjie Guo; Xiaolong Lu; Hameer Chand; Changyong Zhang (Water Research X)
Electrochemical recovery of phosphorus (P) from waste sludge presents a sustainable solution to mitigate the depletion of P rock reserves. However, its feasibility and cost have been persistent challenges. This study introduces an innovative strategy for simultaneous electrochemical leaching, enrichment, and recovery of P (ELER) from poly-aluminum chloride (PAC) sludge with minimal chemical and energy input. A high P leaching efficiency of 90.5% was achieved within the cathode chamber through the rapid elevation of pH induced by water electrolysis at an optimal current density of 30 A m−2 during a single 5-hour cycle. The ELER system recovered approximately 68.8% P from the simulated PAC sludge at a specific energy consumption (SEC) of 214.4 kWh kg−1 P. Notably, the selection and composition of the electrolytes played a crucial role in system performances, with Na2SO4 outperforming NaCl in both efficiency and stability. Increasing catholyte concentration or reducing anolyte concentration significantly reduced P leaching and enrichment efficiency. Furthermore, when optimized for continuous operation over five successive cycles, the system can achieve an ultimate P enrichment efficiency of 96.5% for real PAC sludge, while maintaining a relative low SEC of 54.1 kWh kg−1 P. The enriched P was crystallized as high-purity vivianite, a value-added product that can be utilized as a slow-release P fertilizer or a precursor for lithium-ion battery electrodes. The estimated cost of $4.3 kg−1 P makes this approach economically viable compared to other existing technologies. This innovative approach holds promise for efficient and sustainable P recovery from PAC sludge or other P-rich waste solid.